2017
DOI: 10.18632/oncotarget.14508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the TGFβ-signaling pathway influence expression of miRNAs in colon and rectal normal mucosa and tumor tissue

Abstract: The TGF-β signaling pathway is involved in regulation of cell growth, angiogenesis, and metastasis. We test the hypothesis that genetic variation in the TGF-β signaling pathway alters miRNA expression.We use data from 1188 colorectal cancer cases to evaluate associations between 80 SNPs in 21 genes.Seven variants eIF4E rs12498533, NFκB1 rs230510, TGFB1 rs4803455, TGFBR1 rs1571590 and rs6478974, SMAD3 rs3743343, and RUNX1 rs8134179 were associated with expression level of miRNAs in normal colorectal mucosa. RUN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(63 reference statements)
1
22
0
Order By: Relevance
“… 23 Additionally, this signaling pathway is also involved in both angiogenesis and inflammation. 24 The TGF-β signaling pathway has the ability to mediate the intracellular actions of proinflammatory cytokines, including the activation of nuclear factor-kappa B (NFκB). Deficiency in TGF-β has been witnessed in the progression of extensive inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Additionally, this signaling pathway is also involved in both angiogenesis and inflammation. 24 The TGF-β signaling pathway has the ability to mediate the intracellular actions of proinflammatory cytokines, including the activation of nuclear factor-kappa B (NFκB). Deficiency in TGF-β has been witnessed in the progression of extensive inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TGFβ-signaling pathway appears to be important for CRC, few studies have looked at this pathway with miRNAs. We have previously examined miRNA expression with SNPs in 21 genes associated with the TGFβ-signaling pathway and found that expression of several miRNAs varied by SNPs in TGFβ1 in normal mucosa [ 32 ]. Additionally, other groups have found that specific miRNAs play a significant role in CRC via the TGFβ pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that C‐509T polymorphism is significantly associated with a higher plasma concentration of TGFB1 . In addition, there was a significant correlation between the TGFB1 (rs4803455) mRNA expression and normal colorectal mucosa, supporting the notion of transforming growth factor beta signaling pathway involvement in carcinogenic process of colorectal cancer . Previous findings in patients with high myopia also showed that rs4803455, tag SNP in intron 2 suggested a functional effect for genuine causative variants in linkage disequilibrium in TGFB1 …”
Section: Discussionmentioning
confidence: 77%
“…27,28 In addition, there was a significant correlation between the TGFB1 (rs4803455) mRNA expression and normal colorectal mucosa, supporting the notion of transforming growth factor beta signaling pathway involvement in carcinogenic process of colorectal cancer. 29 Previous findings in patients with high myopia also showed that rs4803455, tag SNP in intron 2 suggested a functional effect for genuine causative variants in linkage disequilibrium in TGFB1. 30 Previously, we had published a trend of increased gastric TGFB1 mRNA expression in patients with FD (P = .09) and showed negative association with HADS compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 96%